Longitudinal Trajectories of Participant- and Study Partner-Rated Cognitive Decline, in Relation to Alzheimer’s Disease Biomarkers and Mood Symptoms - Munro, Catherine E.; Buckley, Rachel; Vannini, Patrizia; DeMuro, Carla; Sperling, Reisa; Rentz, Dorene M.; Johnson, Keith; Gatchel, Jennifer R.; Amariglio, Rebecca (Frontiers in Aging Neuroscience, 2022)
While discrepancies between participant- and study-partner-reported cognitive concerns on the Alzheimer’s disease (AD) continuum have been observed, more needs to be known regarding the longitudinal trajectories of participant- vs. study-partner-reported concerns, particularly their relationship to AD biomarkers and mood symptomology. Additionally, it is unclear whether years of in-clinic data collection are needed to observe relationships with AD biomarkers, or whether more frequent, remote assessments over shorter periods of time would suffice. This study primarily sought to examine the relationships between longitudinal trajectories of participant- and study-partner-rated cognitive decline and baseline biomarker levels (i.e., amyloid and tau positron emission tomography), in addition to how mood symptomatology may alter these trajectories of concerns over a 2-year period. Baseline mood was associated with longitudinal participant-rated concerns, such that participants with elevated depression and anxiety scores at baseline had decreasing concerns about cognitive decline over time (fixed estimate=-0.17, 95%CI[-0.29-(-)0.05], t=-2.75, df=457, adj. p=0.012). A significant interaction between baseline amyloid (fixed estimate=4.07, 95%CI[1.13-7.01], t=2.72, df=353, adj. p=0.026) and tau (fixed estimate=3.50, 95%CI[0.95-6.06], t=2.70, df=331, adj. p=0.030) levels was associated with increasing study-partner concerns, but not participant concerns, over time. The interaction between amyloid and study-partner concerns remained significant when utilizing only the first year of concern-related data collection. Overall, these results suggest that frequent, remote assessment of study-partner reported concerns may offer additional insight into the AD clinical spectrum, as study-partners appear to more accurately update their concerns over time with regard to pathology, with these concerns less influenced by participants’ mood symptomatology.